High Diversity of Genogroup I Picobirnaviruses in Mammals - Woo, Patrick C. Y.; Teng, Jade L. L.; Bai, Ru; Wong, Annette Y. P.; Martelli, Paolo; Hui, Suk-Wai; Tsang, Alan K. L.; Lau, Candy C. Y.; Ahmed, Syed S.; Yip, Cyril C. Y.; Choi, Garnet K. Y.; Li, Kenneth S. M.; et al. (Frontiers in Microbiology, 2016)
In a molecular epidemiology study using 791 fecal samples collected from different terrestrial and marine mammals in Hong Kong, genogroup I picobirnaviruses (PBVs) were positive by RT-PCR targeting the partial RdRp gene in specimens from 5 cattle, 6 monkeys, 17 horses, 9 pigs, 1 rabbit, 1 dog and 12 California sea lions, with 11, 9, 23, 17, 1, 1 and 15 sequence types in the positive specimens from the corresponding animals, respectively. Phylogenetic analysis showed that the PBV sequences from each kind of animal were widely distributed in the whole tree with high diversity, sharing 47.4 to 89.0% nucleotide identities with other genogroup I PBV strains based on the partial RdRp gene. Nine complete segments 1 (viral loads 1.7×104 to 5.9×106/ml) and 15 segments 2 (viral loads 4.1×103 to 1.3×106/ml) of otarine PBVs from fecal samples serially collected from California sea lions were sequenced. In the two phylogenetic trees constructed using ORF2 and ORF3 of segment 1, the nine segment 1 sequences were clustered into four distinct clades (C1 to C4). In the tree constructed using RdRp gene of segment 2, the 15 segment 2 sequences were clustered into nine distinct clades (R1 to R9). In four sea lions, PBVs were detected in two different years, with the same segment 1 clade (C3) present in two consecutive years from one sea lion and different clades present in different years from three sea lions. A high diversity of PBVs was observed in a variety of terrestrial and marine mammals. Multiple sequence types with significant differences, representing multiple strains of PBV, were present in the majority of PBV-positive samples from different kinds of animals.